Learning Peace from the Veranda of Mecca: A Study on the Implementation of the Aceh Youth Volunteer House (3R) Peace Camp Program - Rahadiyand Aditya; Rahmiana Rahman; Istiqomah Istiqomah (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2022)
Several studies have shown that the causes of conflict include the issue of racial differences, ethnic non-uniformity, and even religious affiliation. To suppress conflicts that arise, it is necessary to spread the notion of peace by various parties to the wider community. This study aims to see the implementation of the Peace Camp Program and the response of volunteers to the program. This research method uses descriptive qualitative research with data collection techniques using in-depth interviews, observation, and documentation studies. The findings of this study are the implementation of the Peace Camp Program in the form of a peace school, participating in community activities, small libraries, traditional sports parties, caring for the village environment, and participating in forums in the village. Meanwhile, the volunteer response showed a positive response because it could glue and provide a new understanding of the meaning of the words peace and equality.